Do preschool teachers in Southwest China need more mental health education? An online cross-sectional survey 1 year after the COVID-19 pandemic - Yu, Yao; Wu, Tingting; Gao, Jing; Wang, Shanshan; Zhou, Yang; Zhang, Jiajun (Frontiers in Psychology, 2022)
The study intended to explore the current status of preschool teachers’ psychological problems in Southwest China one year after the COVID-19 pandemic and to assess the association between mental health education and psychological problems and symptoms of psychopathology. 614 preschool teachers from Southwest China were enrolled to complete the questionnaires of the Chinese Symptom Checklist (SCL-90). 60% of the respondents reported psychological distress with GSI T-scores ≥ 63. Especially the high score on obsessive-compulsive disorder, interpersonal sensitivity, and phobic anxiety. Although less than half of the respondents have received mental health education last year, the teachers who received the mental health education reported lower GSI T-scores（β= -1.303,95%CI: -2.208,-0.397). The results demonstrated the significance of constructing the education of promoting preschool teachers’ mental health, and enlightening government or managers of kindergartens to relieve the preschool teachers’ psychological problems through mental health education, especially for those with the pressure of overtime. It’s recommended that local governments or kindergartens should organize more mental health education for kindergarten teachers to improve their mental health as well as their teaching professionalism.